Electromagnetic field energy and radiation intensity in a medium with temporal and spatial dispersion outside the transparency domain - Trigger, S.A.; Zagorodny, A.G. (Вопросы атомной науки и техники, 2018)
Calculation of electromagnetic field energy in a medium with temporal and spatial dispersion outside the transparency domain is discussed. It is shown that charged particle contribution to the energy of electromagnetic perturbations in the general case can be described in terms of a bilinear combination of the dielectric polarizability of the medium. The explicit form of such contribution is found. The relations obtained are used to generalize the Planck law and Kirchhoff law to the case of an absorptive medium with spatial dispersion.